2016
DOI: 10.1007/s00330-016-4524-y
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal aortic aneurysm follow-up by shear wave elasticity imaging after endovascular repair in a canine model

Abstract: • SWI has the potential to detect endoleaks in post-EVAR follow-up. • SWI has the potential to characterize thrombus organization in post-EVAR follow-up. • SWI may be combined with DUS in post-EVAR surveillance of endoleak.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…This imaging technique consistently provided the elastic modulus within the different ROIs. As previously reported in a primary endoleak model, SWI can detect endoleak with a high sensitivity [ 10 ]. In the current study, its potential to detect residual endoleak after embolisation is confirmed.…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…This imaging technique consistently provided the elastic modulus within the different ROIs. As previously reported in a primary endoleak model, SWI can detect endoleak with a high sensitivity [ 10 ]. In the current study, its potential to detect residual endoleak after embolisation is confirmed.…”
Section: Discussionmentioning
confidence: 53%
“…SWI was used to observe the evolution of the mechanical property of the thrombus and embolisation agent over time. Endoleak on SWI was defined as the absence of elasticity values within the aneurysm sac outside the stent-graft with the presence of signal on the posterior wall [ 10 ]. Areas without signal on the posterior wall were deemed as non-diagnostic.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations